Concepção e julgamento moral de docentes sobre bullying na escola - Gonçalves, Catarina Carneiro (2011)
Situations of bullying at school have become one of the largest concerns of educators and other professionals involved in education, due to reaching the student body in various ages and in high proportions, coming to be identified as the greatest manifestation of school violence in Brazil. Explaining the understandings of teachers about the causes, features and actions to combat this problem is an important passage to discuss the role of teachers in bullying, since they are the most responsible ones for interventions and overcoming this issue. Accordingly, this research presents its main objective as understanding and discussing the moral judgments of teachers (from a private school in the Metropolitan region of Recife) on school bullying. In order to do so, 17 active educators of basic education were chosen from a voluntary participation in a meeting on continuing education on school bullying. Data were analyzed qualitatively, based on the enunciation analysis according to Bardin (1979), taking the theoretical assumptions of moral psychology and Cultural Studies of Education into account. Research results point out that a creed for teachers exists that the problem is the sole responsibility of the family, what leads to a difficulty in defining ways to overcome this violence, practices related to the installation of a cooperative environment in classrooms. This can best be understood due to have found a necessary understanding about bullying behaviour among teachers, who equate the behaviour of school violence to a lack of domestic education (which leads to possible thinking about an intervention as exclusively being the family´s responsibility). Moreover, in case of targets of bullying, it can be argued that there is a responsibility of the individual who is victimized at school, and that´s why teachers consider themselves exempt from the responsibility to act in confronting the problem, as they blame the target for the process of victimization. This way of thinking, quite heteronymous, helps spreading the belief that violence can be justified.